2005
DOI: 10.1016/s1472-6483(10)60947-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic injection of spermatozoa and spermatogenic cells: its biology and applications in humans and animals

Abstract: Intracytoplasmic sperm injection (ICSI) has become the method of choice to overcome male infertility when all other forms of assisted fertilization have failed. Animals in which ICSI has produced normal offspring include many species. Success rate with normal spermatozoa is well above 50% in the mouse but ICSI success rates in other animals have been low, ranging from 0.3 to 16.5%. Mouse ICSI revealed that spermatozoa that cannot participate in normal fertilization can produce normal offspring by ICSI, provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
15

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 378 publications
1
120
0
15
Order By: Relevance
“…Removal of acrosomes is a key to success of hamster ICSI. Although ICSI has been successful for many other species (24), no systematic study has been conducted to determine whether the presence or absence of the acrosomes in spermatozoa affects the outcome of ICSI. Here, we report that mouse oocytes became deformed and cytolyzed when three or more acrosome-intact mouse spermatozoa were injected into each oocyte.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal of acrosomes is a key to success of hamster ICSI. Although ICSI has been successful for many other species (24), no systematic study has been conducted to determine whether the presence or absence of the acrosomes in spermatozoa affects the outcome of ICSI. Here, we report that mouse oocytes became deformed and cytolyzed when three or more acrosome-intact mouse spermatozoa were injected into each oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Fortune has smiled on human and mouse ICSI because the acrosomes of these species happen to be rather small (24). If human sperm acrosomes were as large as hamster or bull sperm acrosomes and if human oocytes (Ϸ7 ϫ 10 5 m 3 ) were as small as mouse oocytes (Ϸ2.7 ϫ 10 5 m 3 ), human ICSI could have been problematic from its inception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that they may interfere with sperm chromatin remodeling [19][20][21][22]. Regardless, live offspring have been born using ICSI in a variety of species, including humans and mice [23]. However, existing reports on higher incidence of chromosome aberrations [24] and lower developmental potentials [25,26] in embryos produced by ICSI indicate that further evaluations on the effects of the incorporation of the acrosome into the oocyte are needed.…”
Section: Introductionmentioning
confidence: 99%
“…M illions of years of evolution leading to a well orchestrated series of events for sperm transport and selection in the female tract and sperm-egg interaction during fertilization can be bypassed by the direct microinjection of spermatozoa into oocytes to alleviate infertility or for the experimental manipulation of model animals (1). Since its introduction in humans (2), many thousands of children have been born by using intracytoplasmic sperm injection (ICSI).…”
mentioning
confidence: 99%